2002
DOI: 10.1039/b202087b
|View full text |Cite
|
Sign up to set email alerts
|

Selective partial oxidation in supercritical water: the continuous generation of terephthalic acid from para-xylene in high yield

Abstract: The continuous selective oxidation of p-xylene (p-X) by O 2 (generated by thermal decomposition of aqueous H 2 O 2 ) catalyzed by MnBr 2 in supercritical H 2 O at ca. 400 °C is reported for the first time. The selectivity for terephthalic acid (TA) is > 90%. Compared to existing industrial processes, the reaction has the potential for a significant increase in energy efficiency and a substantial reduction in waste. This reaction is significant because the presence of H 2 O lowers the catalytic activity of MnBr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
90
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(96 citation statements)
references
References 29 publications
4
90
1
Order By: Relevance
“…[1,15] In supercritical water oxidation, the same products have been seen for p-xylene. [11,16] Similarly, in subcritical batch aerobic oxidation of toluene, m-xylene, oxylene, mesitylene (1,3,5-trimethylbenzene), and ethylbenzene, the same intermediates and products have been reported which have also been seen in metal/ bromide-catalysed autoxidation in acetic acid. [1,17] The response to increases in catalyst concentration, temperature, and reaction time reported in scH 2 O are similar to …”
Section: Resultsmentioning
confidence: 81%
See 2 more Smart Citations
“…[1,15] In supercritical water oxidation, the same products have been seen for p-xylene. [11,16] Similarly, in subcritical batch aerobic oxidation of toluene, m-xylene, oxylene, mesitylene (1,3,5-trimethylbenzene), and ethylbenzene, the same intermediates and products have been reported which have also been seen in metal/ bromide-catalysed autoxidation in acetic acid. [1,17] The response to increases in catalyst concentration, temperature, and reaction time reported in scH 2 O are similar to …”
Section: Resultsmentioning
confidence: 81%
“…The continuous oxidation was carried out in scH 2 O with MnBr 2 as the catalyst, using the optimised conditions previously reported by us for the oxidation of p-xylene to terephthalic acid. [11] The expected products and reactivity of methylaromatic compounds in the metal/bromide-catalysed autoxidation of methylaromatics in acetic acid have been detailed in the literature. [1] To a first approximation, the methyl groups are consecutively oxidised to their aromatic acids.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(3) The combination of corrosive bromide as a catalyst component and a high operating temperature requires the use of highly resistant but expensive titanium reactors. A recent breakthrough made by Poliakoff et al, 4 Savage et al 5 and Fulton et al 6 has shown that this reaction can be effectively catalyzed by MnBr 2 with pure O 2 in a new reaction mediumhigh temperature and supercritical water, thus circumventing the use of acetic acid. However, the scope of such reaction systems is limited by the even harsher reaction conditions (T = 300-400…”
Section: Introductionmentioning
confidence: 99%
“…Under certain conditions, the Co/Zr(acac) 4 catalyzed oxidation did not work at all with N 2 /O 2 but proceeded effectively with CO 2 /O 2 , affording high yields of benzoic acid. In this work, we extend the CO 2 effect to this important industrial TPA process, which is extremely challenging because of much higher temperatures and the complexity of intermediates.…”
mentioning
confidence: 99%